2020
DOI: 10.14393/rbcv72n2-48890
|View full text |Cite
|
Sign up to set email alerts
|

Edaphoclimatic Zoning: Methodology and Application to Apple Cultivation in a Brazilian Watershed

Abstract: The planning of land use and occupation is essential when it comes to seeking the best results in view of socioeconomic and environmental sustainability. In this context, Geographic Information Systems are tools that allow, through mapping, to identify physical and climatic characteristics aiming at the best result for a particular crop, which characterizes the edaphoclimatic zoning. This article aimed to elaborate and apply a methodology to create an edaphoclimatic zoning, focused on apple cultivation, having… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 3 publications
0
7
0
1
Order By: Relevance
“…Research has suggested different types of environmental zoning [5,12,15,16,24,27]. Designing EZ must be done according to the economic, social, environmental, political, and institutional needs of the inhabitants in the watershed.…”
Section: Environmental Zoning (Ez)mentioning
confidence: 99%
See 3 more Smart Citations
“…Research has suggested different types of environmental zoning [5,12,15,16,24,27]. Designing EZ must be done according to the economic, social, environmental, political, and institutional needs of the inhabitants in the watershed.…”
Section: Environmental Zoning (Ez)mentioning
confidence: 99%
“…Watershed management has evolved through various stages of social development, starting with a local problem and extending to larger territorial issues [2,10,11]. Watershed management addresses anthropic problems [7], current land use [12], land use conflicts [13], excessive use of ecological resources [9], biological resources [14], water resources [15]. To solve these problems, watershed management employs multiple evaluation criteria, among them are the potential areas of intervention that can be addressed via environmental zoning (EZ) [9,10,16].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…O zoneamento edafoclimático é uma ferramenta importante de planejamento agrícola e tomadas de decisões, assim, reduzindo riscos de perdas no cultivo, uma vez que avalia a compatibilidade entre as espécies e o ambiente, caracterizando regiões com maior ou menor aptidão, contribuindo para o planejamento de políticas públicas que beneficiam o desenvolvimento socioeconômico da região (Santos et al, 2020). Dessa forma, se faz importante uma avaliação do zoneamento de aptidão edafoclimática como representação das condições atuais de cultivo da bananeira no Nordeste brasileiro, que se situa como um importante centro na produção frutícola.…”
Section: Congresso Norte Nordeste De Ciências Agrárias (Online) -Avanço Tecnológico E Sustentabilidadeunclassified